THE FUTURE OF TRANSPORTATION: A COMPREHENSIVE ANALYSIS OF ELECTRIC VEHICLES AND THEIR IMPACT ON SUSTAINABILITY, ECONOMY, AND SOCIETY - Butkar, Umakant Dinkar; Sabale, Rajendra Parshram; Patil, Prakash Chhagan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper provides a comprehensive analysis of electric vehicles (EVs), focusing on their environmental, economic, and societal impacts. With the growing concern over climate change, EVs are positioned as a cleaner, more sustainable alternative to conventional internal combustion engine vehicles. This paper examines the technological advancements, challenges in mass adoption, the environmental benefits, the economic implications, and the social shifts required for widespread adoption of EVs. The analysis draws on data from recent studies, industry reports, and government policies to present an integrated view of the future of electric mobility.